Family medicine journals’ endorsement of reporting guidelines and clinical trial registration: a cross-sectional analysis - Wyatt Compton; Brody Dennis; Payton Clark; Caleb A Smith; Danya Nees; Griffin Hughes; Matt Vassar (BJGP Open)
Background: Family medicine, vital for patient care but underfunded, prompts an evaluation of how family medicine journals endorse, require, and advocate for reporting guidelines (RGs), clinical trial, and systematic review registration. Aim: Assess endorsement and requirement of RGs, and the stance on registration of clinical trials and systematic reviews in family medicine journals, impacting research quality and transparency. Design & setting: A cross-sectional analysis of 43 ‘family practice’ journals, identified through the 2021 Scopus CiteScore, was undertaken. Editors-in-chief were contacted to confirm article types. Data extracted from ‘instructions to authors’ pages focused on recommendations or requirements for use of RGs, and for trial registration. Method: To ensure confidentiality and prevent bias, authors independently extracted data on the requirement or recommendation for use of RGs and clinical trial registration to provide an overview of research standards. Results: From the 43 journals, the most recommended guidelines were CONSORT (69%), PRISMA (58%), and STROBE (60%). The most required were PRISMA (16%) and CONSORT (11%). Clinical trial registration was recommended or required by 67% of journals. Additionally, 40 out of the 43 (93%) journals cited at least one reporting guideline in their instructions to authors. Conclusion: Family medicine journals exhibit a variety of endorsement and requirement patterns for RGs and clinical trial registration. While guidelines like CONSORT, PRISMA, and STROBE are acknowledged, caution is needed in presuming a direct link between mention of these RGs and enhanced research quality. A nuanced approach, promoting diverse RGs and rigorous study registration, is essential for elevating transparency and advancing research standards in family medicine.